1960
DOI: 10.1192/bjp.106.443.638
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Electric Convulsive Treatments on Nitrogen, Calcium, and Phosphorus Metabolism in Psychiatric Patients

Abstract: This investigation was designed to determine whether significant alterations in the metabolism of nitrogen, calcium, and phosphorus occur in psychiatric patients during the therapeutic administration of electric convulsive treatments. Gour and Chaudhry (1) observed transient changes in serum calcium following grand mal convulsions in a series of patients. Jarvie and Mulligan (2), repeating this experiment in patients receiving muscular relaxants during the administration of E.C.T., failed to demonstrate simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In addition, changes in serum or CSF calcium levels have been reported in patients with depression not directly associated with endocrine dysfunction 32–40. Conversely, reduced plasma, serum, or CSF calcium levels accompany improvement of depressive symptomatology after either electroconvulsive shock or antidepressant drug treatment 33–35,39,41–43. Finally, calcium channel antagonists have been reported to be antidepressant in an anecdotal report 44,45…”
Section: Major Depression and Excitatory Amino Acidsmentioning
confidence: 99%
“…In addition, changes in serum or CSF calcium levels have been reported in patients with depression not directly associated with endocrine dysfunction 32–40. Conversely, reduced plasma, serum, or CSF calcium levels accompany improvement of depressive symptomatology after either electroconvulsive shock or antidepressant drug treatment 33–35,39,41–43. Finally, calcium channel antagonists have been reported to be antidepressant in an anecdotal report 44,45…”
Section: Major Depression and Excitatory Amino Acidsmentioning
confidence: 99%
“…Clinical studies have shown that Ca is associated with a mental disorders ( 33 , 34 ). Rare studies have directly examined the relationship between Ca intake and depression separately ( 35 , 36 ).…”
Section: Introductionmentioning
confidence: 99%